Лазер на парах иодида меди с внутренним реактором; Оптика атмосферы и океана; Т. 25, № 8 - Шиянов Д. В. Дмитрий Валерьевич; Суханов В. Б. Виктор Борисович; Евтушенко Г. С. Геннадий Сергеевич; Ткаченко Н. Ю. Николай Юрьевич (2012, 2012)
Заглавие с экрана